ANALISIS PENGARUH LIKUDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FARMASI DI BEI - Elbertina Manulang; Anggi Pratama; Mika Debora BR. Barus (Ensiklopedia Education Review, 2021)
This study aims to determine and analyze the effect of liquidity and profitability and on firm value in pharmaceutical companies listed on the Indonesia Stock Exchange. This type of research is causal associative. The population of this research is pharmaceutical companies listed on the Indonesia Stock Exchange from 2011 to 2020. The sampling method is census, so the number of samples used is 30 sample data. The data analysis method used multiple linear regression. The results show that profitability has a positive and partially significant effect on firm value in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). Meanwhile, liquidity does not partially affect the value of the company, in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). profitability and liquidity simultaneously have a significant effect on firm value in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX).Keywords: Profitability, Liquidity, Firm Value.